Dampak Teknologi dan Media Sosial terhadap Isu Gender dan HAM dalam komunitas Muslim - Miftaku Ni’amah; Mariana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This abstract aims to examine the impact of technology and social media on gender and human rights issues within the Muslim community, particularly in the context of changing religious and social discourse in the digital era. This study employs library research methods by analyzing various written sources in the form of academic books, scientific journal articles, research reports, and works by Islamic thinkers and human rights studies relevant to the topics of gender, technology, and social media. Data are analyzed descriptively and analytically by linking Islamic perspectives, social theory, and human rights principles to gain a comprehensive understanding. The results show that technology and social media play a dual role: as a means of education, advocacy, and empowerment in strengthening awareness of gender equality and respect for human rights, while also serving as a space with the potential to cause polarization, misinformation, and the strengthening of gender-biased religious interpretations. Therefore, the integration of Islamic values ​​based on justice, digital ethics, and humanity is key to optimizing the use of technology to contribute positively to upholding gender and human rights within the Muslim community.